High grade gliomas in young children: The South Thames Neuro-Oncology unit experience and recent advances in molecular biology and targeted therapies. (17th November 2021) - Pearce, Janice; Khabra, Komel; Nanji, Henry; Stone, Joanna; Powell, Karen; Martin, Danielle; Zebian, Bassel; Hettige, Samantha; Reisz, Zita; Bodi, Istvan; Al-Sarraj, Safa; Bridges, Leslie R.; et al.
Abstract: High grade gliomas (HGG) have a dismal prognosis with survival rates of 15–35%. Approximately 10–12% of pediatric HGG occur in young children and their molecular biology and clinical outcomes differ from those arising at older ages. We report on four children aged <5 years newly diagnosed with non-brainstem HGG between 2011 and 2018 who were treated with surgery and BBSFOP chemotherapy. Two died of tumor progression. The other two are still alive without radiotherapy at 3.8 and 3.9 years from diagnosis: one of whom remains disease-free off treatment; and the other one, whose tumor harbored a KCTD16:NTRK2 fusion, went on to receive larotrectinib. Additionally we review the general management, outcomes and latest updates in molecular biology and targeted therapies for young children with HGG. Infant gliomas can be stratified in molecular subgroups with clinically actionable oncogenic drivers. Chemotherapy-based strategies can avoid or delay the need for radiotherapy in young children with HGG. Harnessing the potential of NTRK, ALK, ROS1 and MET inhibitors offers the opportunity to optimize the therapeutic armamentarium to improve current outcomes for these children.